From Metallic LnTt (Ln = La, Nd; Tt = Si, Ge, Sn) to Electron‐precise Zintl Phase Hydrides LnTtH. Issue 22 (17th April 2018) - Werwein, Anton; Auer, Henry; Kuske, Lena; Kohlmann, Holger
Abstract : LnTt ( Ln = La, Nd; Tt = Si, Ge, Sn) compounds crystallize in the CrB‐ or the FeB‐structure type with 1 ∞ [ Tt 2– ]‐polyanionic zigzag chains and can be rationalized as Ln 3+ Tt 2– e – . They take up hydrogen at gas pressures from 10 to 160 bar and temperatures up to 750 K. The hydrides LnTt H1– x (0.04 ≤ x ≤ 0.39) crystallize either in a hydrogen filled CrB‐structure type (ZrNiH type, C ‐phase, Cmcm : LaSiD0.92(1), LaGeD0.88(1), NdSiD, NdGeD0.95(1), LaSnH x ) or in a hydrogen filled FeB‐structure type (LaGeH type, P ‐phase, Pnma : LaSiD0.61(3), LaGeD0.96(4), NdSiD0.88(6) ). In both cases, hydrogen atoms partially fill tetrahedral Ln 4 voids as proven by neutron powder diffraction. While CrB‐structure type LnTt reacts to C ‐phase only, FeB‐structure type LnTt hydrogenates to mixtures of C ‐ (major phase) and P ‐type hydrides. Electronic structure calculations reveal the depopulation of Ln ‐d states, which cause the metallic conductivity in LnTt to be the main electronic effect upon hydrogenation. They further suggest Zintl phase hydrides LnTt H to be still poor metallic conductors with a pseudo bandgap at the Fermi level. The hydrogenation reaction from LnTt to LnTt H may thus be regarded as an incomplete metal to semiconductor transition. Abstract :